Wide-area transepithelial sampling with computer-assisted analysis to detect high grade dysplasia and cancer in Barrettʼs esophagus: a multicenter randomized study - van Munster, Sanne N.; Leclercq, Philippe; Haidry, Rehan; Messmann, Helmut; Probst, Andreas; Ragunath, Krish; Bhandari, Pradeep; Repici, Alessandro; Munoz-Navas, Miguel; Seewald, Stefan; Lemmers, Arnaud; Fernández-Esparrach, Glòria; Pech, Oliver; Schoon, Erik J.; Kariv, Revital; Neuhaus, Horst; Weusten, Bas L. A. M.; Siersema, Peter D.; Correale, Loredana; Meijer, Sybren L.; de Hertogh, Gert; Bergman, Jacques J.G.H.M.; Hassan, Cesare; Bisschops, Raf (Endoscopy, 2022)
Background Current surveillance for Barrett’s esophagus (BE), consisting of four-quadrant random forceps biopsies (FBs), has an inherent risk of sampling error. Wide-area transepithelial sampling (WATS) may increase detection of high grade dysplasia (HGD) and esophageal adenocarcinoma (EAC). In this multicenter randomized trial, we aimed to evaluate WATS as a substitute for FB.Methods Patients with known BE and a recent history of dysplasia, without visible lesions, at 17 hospitals were randomized to receive either WATS followed by FB or vice versa. All WATS samples were examined, with computer assistance, by at least two experienced pathologists at the CDx Diagnostics laboratory. Similarly, all FBs were examined by two expert pathologists. The primary end point was concordance/discordance for detection of HGD/EAC between the two techniques.Results 172 patients were included, of whom 21 had HGD/EAC detected by both modalities, 18 had HGD/EAC detected by WATS but missed by FB, and 12 were detected by FB but missed by WATS. The detection rate of HGD/EAC did not differ between WATS and FB (P = 0.36). Using WATS as an adjunct to FB significantly increased the detection of HGD/EAC vs. FB alone (absolute increase 10 % [95 %CI 6 % to 16 %]). Mean procedural times in minutes for FB alone, WATS alone, and the combination were 6.6 (95 %CI 5.9 to 7.1), 4.9 (95 %CI 4.1 to 5.4), and 11.2 (95 %CI 10.5 to 14.0), respectively.Conclusions Although the combination of WATS and FB increases dysplasia detection in a population of BE patients enriched for dysplasia, we did not find a statistically significant difference between WATS and FB for the detection of HGD/EAC as single modality.